Implementasi Metode At-Taisir dalam Pembelajaran Tahfizh di Pondok Pesantren Mu’allimin Muhammadiyah Taajul Huffazh Pakan Sinayan - Rizki Wahyudi; Muhiddinur Kamal (PT. Pustaka Cendekia Publisher, 2024)
A unique educational approach is carried out at the Mu'allimin Muhammadiyah Taajul Huffazh Pakan Sinayan Islamic Boarding School, one of which is the Taisir teaching method. The teaching approach known as the